DETERMINANT ANALYSIS OF HIGH QUALITY ASSET RATIO USING BANK-SPECIFIC VARIABELS OF 19 COMMERCIAL BANKS IN INDONESIA (2008-2017 PERIOD) - Putri, Nabila Kesuma; Anggono, Achmad Herlanto (Journal of Business and Management, 2018)
Abstract.According to (Basel Committee on Banking Supervision, 2013) the financial crisis that started in 2007 is caused by the poor management of the banks’ liquidity and if not solved with a contingency plan regarding liquidity, could cause them to collapse. This further stresses out the importance of liquidity especially in banking industry. And due to the recent highlight of new regulation issued by the Basel III committee, the liquidity of a bank will be measured with the Liquidity Coverage Ratio, which illustrates the condition of a bank’s liquidity measured by its high quality liquid asset divided to its net cash outflow in 30 days. This is used to measure the bank’s ability and liquidity in times of distress. This regulation showed the importance of banks to hold into their high quality liquid assets. This study uses bank-specific variables such as CAR, NIM, NPL, LDR, and SIZE to examine its relationship towards High Quality Liquid Asset Ratio as the dependent variable. The data used in this research are obtained from quarterly published financial statements of 19 commercial banks in Indonesia from 2008Q1-2017Q4. This research used Fixed Effect model on regression test, and EGLS Panel (cross-section weight) method is used in processing the data used in this research. The result of regression test showed that out of five independent variables, which are CAR, NIM, NPL, LDR, and SIZE, the only variable that does not have a significant effect towards the dependent variable, High Quality Liquid Asset Ratio is CAR. Then, out of the four remaining independent variables, which are NIM, NPL, LDR, and SIZE, the only variable that has a significant negative effect towards High Quality Liquid Asset is SIZE. Other independent variables, NIM, NPL, and LDR resulted in a significantly positive relationship with the dependent variable High Quality Asset Ratio.Keyword: : Liquidity, High Quality Liquid Asset Ratio, Fixed Effect Model Regression